An Introduction to the Role and Limitations of Government Responsibilities in Supporting Higher Education Across Selected Legal Systems - Mohammad Ghasem Tangestani (پژوهشنامه حقوق تطبیقی)
The government's obligation to facilitate, generalize, and provide access to higher education free of charge, in accordance with the country's self-sufficiency, is outlined in Articles 3 and 30 of the Constitution. This mandate has established several legal requirements for the government. Considering that the policy of governments in the higher education system is not necessarily set in a unified form, and also considering the challenges facing the higher education system of Iran, such as the financing of universities, the disproportionality of student admission capacity with the needs of the labor market, the growth of unemployment of graduates of some fields, etc., in this article, we seek to examine the way of reflecting the above task in the selected countries and finally, extracting findings and teachings for the system We are higher education in Iran. Based on the findings of the present study, the right to education and the government's obligation to provide higher education are not enshrined in the constitutions of all countries. By examining the domestic laws and procedures of various countries, it becomes evident that, despite the government's responsibility to regulate the overarching framework of the higher education system, there is no government monopoly on the provision of these services. Furthermore, free higher education cannot be regarded as a universally accepted principle in this domain. Thirdly, when adopting a systemic approach to the aforementioned issue, the regulation of government policy in the realm of higher education should be informed by the theoretical framework of the state within the target society, as well as the implications of such policies on other social and economic initiatives. Given the substantial quantitative growth of higher education in Iran and the challenges it encounters; it is essential to reassess the parameters of higher education development in alignment with the country's pursuit of self-sufficiency.